Progress of the Novel Genre in the Current Literary Process - SHaxnoza Buriyeva Alisher qizi (Zien Journals, 2022)
This article discusses the contribution of novels created in the Uzbek literary process from independence to the present to the development of the novel genre.
Keywords: Plot; psychological; subjective effect; perspective